EPONYMS IN INTERNAL MEDICINE: PLATELET-VASCULAR HEMOSTATIC DISORDERS - D. V. Bukhtoyarov; A. A. Kondrashov (Klinicist)
The paper considers platelet-vascular hemostatic disorders, describes the clinical presentation and diagnosis of major nosological entities, and gives their eponymic names.